Models of care for osteoporosis: A systematic scoping review of efficacy and implementation characteristics. (August 2021) - Jones, Alicia R.; Herath, Madhuni; Ebeling, Peter R.; Teede, Helena; Vincent, Amanda J.
Abstract: Background: Osteoporosis affects over half of adults over 50 years worldwide. With an ageing population, osteoporosis, fractures and their associated costs are increasing. Unfortunately, despite effective therapies, many with osteoporosis remain undiagnosed and untreated. Models of care (MoC) to improve outcomes include fracture liaison services, screening, education, and exercise programs, however efficacy for these is mixed. The aim of this study is to summarise MoC in osteoporosis and describe implementation characteristics and evidence for improving outcomes. Methods: This systematic scoping review identified articles via Ovid Medline and Embase, published in English between 01/01/2009 and 15/06/2021, describing MoC for adults aged ≥18 years with, or at risk of, osteoporosis and / or health professionals caring for this group. All included at least one of clinical, consumer or clinician outcomes, with fractures and bone mineral density (BMD) change the primary clinical outcomes. Exclusion criteria were studies assessing pharmaceuticals or procedures without other interventions, or insufficient operational details. All study designs were included, with no comparator necessary. Title and abstract were reviewed by two reviewers. Full text review and data extraction was performed by these reviewers for 20% of article and, thereafter by a single author. As the review was predominantly descriptive, no comparator statistics were used. Findings: 314 articles were identified describing 289 MoC with fracture liaison services (n =89) and education programs ( n =86) predominating. The population had prior fragility fracture in 77 studies, the median (IQR) patient number was 210 (87, 667) and the median (IQR) follow-up duration for outcome assessment was 12 (6, 12·5) months. Fracture reduction was reported by 65 studies, with 16 (37%) graded as high quality, and 19 / 47 studies with a comparator group found a reduction in fractures. BMD change was reported by 73 studies, with 41 finding improved BMD. Implementation characteristics including reach, fidelity and loss to follow-up were under-reported, and consumer and clinician perspectives rare. Interpretation: This comprehensive review of MoC for osteoporosis demonstrated inconsistent evidence for improving outcomes despite similar types of models. Future studies should include implementation outcomes, consumer and clinician perspectives, and fracture or BMD outcomes with sufficient duration of follow-up. Authors should consider pragmatic trial designs and co-design with clinicians and consumers. Funding: None.